2021
DOI: 10.1111/1462-2920.15789
|View full text |Cite
|
Sign up to set email alerts
|

Ero1‐Pdi1 module‐catalysed dimerization of a nucleotide sugar transporter, FonNst2, regulates virulence of Fusarium oxysporum on watermelon

Abstract: Fusarium oxysporum f. sp. niveum (Fon) is a soilborne fungus causing vascular Fusarium wilt on watermelon; however, the molecular network regulating Fon virulence remains to be elucidated. Here, we report the function and mechanism of nucleotide sugar transporters (Nsts) in Fon. Fon genome harbours nine FonNst genes with distinct functions in vegetative growth, asexual production, cell wall stress response and virulence. FonNst2 and FonNst3 are required for full virulence of Fon on watermelon and FonNst2 is ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 91 publications
3
38
0
Order By: Relevance
“…niveum ( Fon ), is one of the most devastating fungal diseases ( 43 ). It was previously found that an effector, FonSIX6, a CCR4-Not complex subunit, FonNOT2, and a nucleotide sugar transporter, FonNst2, are essential for virulence in Fon ( 44 46 ). The present study aimed to investigate the involvement of protein palmitoylation in Fon virulence and revealed that FonPAT1, FonPAT2, and FonPAT4 are required for virulence in Fon .…”
Section: Introductionmentioning
confidence: 99%
“…niveum ( Fon ), is one of the most devastating fungal diseases ( 43 ). It was previously found that an effector, FonSIX6, a CCR4-Not complex subunit, FonNOT2, and a nucleotide sugar transporter, FonNst2, are essential for virulence in Fon ( 44 46 ). The present study aimed to investigate the involvement of protein palmitoylation in Fon virulence and revealed that FonPAT1, FonPAT2, and FonPAT4 are required for virulence in Fon .…”
Section: Introductionmentioning
confidence: 99%
“…The SUMOylation pathway is critical for stress responses in fungi, including M. oryzae [ 8 , 44 ]. To test whether the SUMOylation pathway has a role in the maintenance of Fon cell wall integrity, we analyzed the effect of three cell wall-perturbing agents, including CR, CFW, and NaCl [ 33 ], on the mycelial growth of the WT, deletion mutants, and complementation strains. When grown on PDA supplemented with 0.2 mg/mL CR, 0.1 mg/mL CFW or 0.5 M NaCl, mycelial growth of the deletion mutants was significantly inhibited compared to WT ( Figure 5 A–D).…”
Section: Resultsmentioning
confidence: 99%
“…To generate the gene replacement constructs, the 5′ and 3′ flanking sequences of the SUMOylation pathway genes were amplified from Fon genomic DNA and fused with the 1349 bp hygromycin gene using the double-joint PCR method. The obtained gene knockout fragments were directly transformed into WT protoplasts [ 32 , 33 ]. The resulting transformants were screened with 100 µg/mL hygromycin B, and were further validated by polymerase chain reaction (PCR), reverse transcriptase (RT)-quantitative PCR, and Southern blotting assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations